(3SQ GdaUGMIs - (3YHO Gddg Hf eMeO Hf SYjO Hf SfGf, CHh eMeO GdNaGLj GdMdHj,J (B466 (3g` s
(3ChdgG (B:s
(3jHJOF HCKfGA aUd ai GdCUhGJ Hbhdg hGdUhJ eYbhd dCfg jOQc s
(3BNQgG (B:s
(3jfJgi Hbhdg hef GdUMI UMI GdebGHdI ai GdeYGOf s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B122 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B120s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B988s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdHdGZIs